2016
DOI: 10.1007/s00276-016-1761-3
|View full text |Cite
|
Sign up to set email alerts
|

Portal supply of segment IV of the liver based on CT-scan

Abstract: Portal vascularization of S4 varies widely (2-8 branches) between patients and originates predominantly from the junction between the left portal vein and the round ligament. There is no anatomical rationale to divide S4 into S4a and S4b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…The findings of this study provide an insight into the impact of the segmental anatomy of LPV on the outcome of various surgical and minimally invasive procedures such as ALPPS and PVE. The presence of multiple portal branches to segment IV, arising not only from UPLPV but also from TPLPV as confirmed in this study, is one of the main reasons for the failure of PVE in achieving desirable increment in the future liver segment (Maurer et al, 2017). We found that the portal branches intended for the segment IV arise from the anterior or superior aspect of TPLPV in about 50% of the cases.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The findings of this study provide an insight into the impact of the segmental anatomy of LPV on the outcome of various surgical and minimally invasive procedures such as ALPPS and PVE. The presence of multiple portal branches to segment IV, arising not only from UPLPV but also from TPLPV as confirmed in this study, is one of the main reasons for the failure of PVE in achieving desirable increment in the future liver segment (Maurer et al, 2017). We found that the portal branches intended for the segment IV arise from the anterior or superior aspect of TPLPV in about 50% of the cases.…”
Section: Discussionsupporting
confidence: 78%
“…Yan et al had also reported the presence of small portal venous branches to segment IV from the transverse portion of left and right portal vein in 80% of the cases on cadaveric dissection (Yan et al, ). However, Maurer et al reported the presence of such branches from TPLPV in only 1.07% of the cases on CT imaging (Maurer et al, ). These differences emphasize the difficulty of the visualization of these small branches on preoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Авторы также отмечают следующую особенность: у пациентов с 2 ветвями к S IV диаметр самого большого сосуда составил в среднем 5,81 мм (3,01-6,69 мм); у пациентов с 8 ветвями -1-2 мм. Замечено, что в случаях с 2 или 3 ветвями портальные ветви к сегменту печени начинаются общим стволом длиной от 9 до 21 мм, далее происходит деление последних и каждый проникает в S IV сегмент отдельным стволом [24].…”
Section: Introductionunclassified